Phenotypic Characterization of Malaysian Village Chicken Ecotypes in Peninsular Malaysia - Abu Bakar, Amie Marini; Samat, Noraini; Ismail Affendee, Azlina Azma; Abdul Razak, Roziatul Erin; Saharani, Nooraisyah; Ayob, Mohd Hafizzudin; Othman, Mohd Firdaus; Mohd Amin, Mohd Hishammfariz; Zulkifli, Nadiatur Akmar; Abdul Razak, Shairah (Malaysian Applied Biology, 2025)
Livestock characterization is vital for effectively developing, breeding and conserving Animal Genetic Resources (AnGR). Beyond breed development, there is a growing need for the livestock genomic sector to become more accessible, ensuring its applications contribute to conservation initiatives as well. This study focused on identification and evaluation of diverse village chicken ecotypes in Peninsular Malaysia based on their distinct phenotypic characteristics. A total of 459 chickens, commonly known as Ayam Kampung, were sampled from 15 different indigenous ecotypes. These chickens were assessed for a range of traits, including plumage color and pattern, comb type and color, as well as beak, and shank color. The findings revealed noticeable physical differences among the ecotypes, with five major groups identified: Arab chickens, cockfighting chickens, Kurik chickens, Naked Neck chickens, and multicolor chickens. The most prevalent traits observed were multicolor plumage, yellow-brown beak, and yellow shank, with red single and pea/walnut comb types also frequently present. These variations, shaped by environmental and human factors, are at risk of disappearing due to disease, human interference, and the introduction of other breeds. The findings of this study provide valuable insights into the morphological characteristics of village chickens, making a significant contribution to future breeding programs. These insights are also crucial for preserving these unique genetic resources, maintaining biodiversity and their sustainable use in the future.